Susceptibility and disease pathogenesis of North American domestic and feral pigs to Japanese encephalitis virus - Park, So Lee (Kansas State University, 2021)
Japanese encephalitis virus (JEV), a mosquito-borne flavivirus capable of causing fatal encephalitis, is maintained in nature between infected mosquitoes and viremic swine and avian species, with humans as a dead-end host. At present, JEV is only endemic to parts of the Asia-Pacific region, but the presence of large numbers of susceptible vertebrate hosts and competent vectors outside its endemic areas is a significant concern in its potential for dispersal into new territories. Previously, North American avian species and Culex species mosquitoes have been shown to be susceptible and competent for JEV transmission. A critical but missing gap of knowledge is whether or not the swine species in the United States are also susceptible to JEV. The objective of this dissertation was to address this important research gap and determine the susceptibility profile and pathogenesis of JEV in North American pigs. Three specific aims were pursued to test the central hypothesis that North American domestic and feral pigs are susceptible to JEV and can potentially support its transmission. In Aim 1, the susceptibility of North American domestic pigs to JEV was determined through the invasive challenge of intravenous inoculation. All pigs became viremic, seroconverted, and developed similar pathologic outcomes as observed in published studies. In Aim 2, our approach was to mimic the natural route of transmission more closely via intradermal inoculation. In the same experiment, mosquito salivary gland extract (SGE) was inoculated with infectious viruses to investigate the effects of mosquito saliva in the disease pathogenesis of JEV. Piglets were simultaneously co-inoculated with JEV and SGE to recapitulate the actual infection route in nature. In contrast to the enhanced virus infection and disease severity reported in mice, the presence of mosquito saliva in the JEV inoculation altered the fever and viral nasal shedding kinetics but, interestingly, did not impact the dynamics and severity of viremia, clinical signs, and neuroinvasion. Lastly, Aim 3 was conducted to establish a feral pig model for JEV, using the Sinclair miniature research swine that has been bred to have a feral genotypic and phenotypic background. Intradermal JEV challenge of these pigs resulted in high viremia, viral nasal shedding, and systemic dissemination comparable to JEV infection in domestic pigs. Together, our results indicate that many potential enzootic hosts needed for JEV transmission cycle are present in North America. These findings provided a better understanding of how JEV behaves in its enzootic hosts – the domestic and feral pigs. The work presented in this dissertation provides valuable data and novel animal models of JEV to further our understanding of this significant pathogen and contribute to the development of effective countermeasures to ultimately protect the public health and the agricultural industry.
Keywords: Japanese encephalitis virus; Pig; Pathogenesis; Susceptibility; Mosquito saliva